EMMPRIN/CD147-encriched membrane vesicles released from malignant human testicular germ cells increase MMP production through tumor–stroma interaction - Milia-Argeiti, Eleni; Mourah, Samia; Vallée, Benoit; Huet, Eric; Karamanos, Nikos K.; Theocharis, Achilleas D.; Menashi, Suzanne (Biochimica et biophysica acta, 2014)
Elevated levels of EMMPRIN/CD147 in cancer tissues have been correlated with tumor progression but the regulation of its expression is not yet understood. Here, the regulation of EMMPRIN expression was investigated in testicular germ cell tumor (TGCTs) cell lines. EMMPRIN expression in seminoma JKT-1 and embryonal carcinoma NT2/D1 cell lines was determined by Western blot, immunofluorescence and qRT-PCR. Membrane vesicles (MVs) secreted from these cells, treated or not with EMMPRIN siRNA, were isolated by differential centrifugations of their conditioned medium. MMP-2 was analyzed by zymography and qRT-PCR. The more aggressive embryonic carcinoma NT2/D1 cells expressed more EMMPRIN mRNA than the seminoma JKT-1 cells, but surprisingly contained less EMMPRIN protein, as determined by immunoblotting and immunostaining. The protein/mRNA discrepancy was not due to accelerated protein degradation in NT2/D1 cells, but by the secretion of EMMPRIN within MVs, as the vesicles released from NT2/D1 contained considerably more EMMPRIN than those released from JKT-1. EMMPRIN-containing MVs obtained from NT2/D1, but not from EMMPRIN-siRNA treated NT2/D1, increased MMP-2 production in fibroblasts to a greater extent than those from JKT-1 cells. The data presented show that the more aggressive embryonic carcinoma cells synthesize more EMMPRIN than seminoma cells, but which they preferentially target to secreted MVs, unlike seminoma cells which retain EMMPRIN within the cell membrane. This cellular event points to a mechanism by which EMMPRIN expressed by malignant testicular cells can exert its MMP inducing effect on distant cells within the tumor microenvironment to promote tumor invasion. This article is part of a Special Issue entitled Matrix-mediated cell behaviour and properties. •The more aggressive testicular embryonic carcinoma cells express more EMMPRIN than seminoma cells•They preferentially target EMMPRIN to secreted membrane vesicles•Greater uptake of EMMPRIN in vesicles increases proteolytic potential in fibroblasts•Hence, vesicular EMMPRIN can potentiate tumor–stroma cooperation at a distance